Mechanism of Damage and Deterioration of Red Sandstone in South China under Different pH Treatments - Shuguang Zhang; Shutian Zhao; Jiaqi Liu; Zhifeng Liu; Dipeng Zhu; Yingbo Li (Advances in Civil Engineering)
Groundwater in southern China region contains various chemical compositions. By comparing the effects of acidic, neutral, and alkaline solutions on mechanical properties and internal structure, the changes in mechanical parameters and microstructure of chemical solution etched samples were obtained. The results show that as the pH of the solution increases from 2 to 12, the peak strength and elastic modulus of the rock samples initially increase and then decrease, while axial strain and Poisson’s ratio first decrease and then increase. The degree of deterioration of rock samples by different chemical solutions follows the order strong acid (pH ≤ 4) > strong alkali (pH ≥ 10) > weak acid (4 < pH ≤ 6) > weak alkali (8 ≤ pH < 10) > neutral (pH = 7). Alkaline and neutral solutions mainly corrode the surface of rock samples, with the wave velocity of the rock core higher than that of the surface. The wave velocities of alkaline solutions at different pH values after corrosion are essentially the same as that of pH = 7 neutral solution, ~2,850 m/s. Acidic solutions corrode both the surface and core of rock samples, with the wave velocities of the core and surface being similar. After corrosion by pH = 2 acidic solution, the wave velocity of the rock samples decreases to 2,505 m/s. With increasing acidity or alkalinity of the chemical solution, the internal pores of the rock transition from micropores to mesopores and macropores. Compared to pH = 7 neutral solution, the porosity of rock samples increases by 59.13% and 24.17% after corrosion by pH = 2 and pH = 12 solutions, respectively. Acidic and alkaline solutions exhibit distinct mechanisms: acidic solutions corrode particles and framework to form continuous fractures, whereas alkaline solutions generate new substances filling the fractures through hydration reactions. By introducing chemical damage variables and considering threshold factors, a chemical damage constitutive model is constructed to effectively describe the impact of chemical corrosion on mechanical properties. This systematic study of the chemical environment’s influence on internal structures reveals the erosion mechanisms of acidic, alkaline, and neutral saline solutions, which is crucial for the stability of underground engineering surrounding rocks and geological disaster prevention in southern China.